2016
DOI: 10.1038/ni.3522
|View full text |Cite
|
Sign up to set email alerts
|

Affinity for self antigen selects Treg cells with distinct functional properties

Abstract: How regulatory T cells (Treg cell) control lymphocyte homeostasis is not fully understood. Here we identify two Treg cell populations with differing degrees of self-reactivity and distinct regulatory functions. Triplehi (GITRhiPD-1hiCD25hi) Treg cell are highly self-reactive and control lympho-proliferation in peripheral lymph nodes. Triplelo (GITRloPD-1loCD25lo) Treg cells are less self-reactive and limit development of colitis by promoting conversion of CD4+ Tconv cells into induced Treg cells (iTreg cells).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 64 publications
8
89
0
1
Order By: Relevance
“…Through the use of conditional TCRα-KO mice, it was recently shown that TCR is essential and is continually required for Treg function; however, it is still unclear whether the level of TCR signaling is proportional to Treg function (17). Several approaches have utilized surrogate markers to distinguish Treg populations with various levels of self-reactivity (22,51). A more recent study used a combination of 3 surface markers to differentiate a population of functional Tregs in models of colitis and immune homeostasis (GITR, CD25, PD-1) (51).…”
Section: Discussionmentioning
confidence: 99%
“…Through the use of conditional TCRα-KO mice, it was recently shown that TCR is essential and is continually required for Treg function; however, it is still unclear whether the level of TCR signaling is proportional to Treg function (17). Several approaches have utilized surrogate markers to distinguish Treg populations with various levels of self-reactivity (22,51). A more recent study used a combination of 3 surface markers to differentiate a population of functional Tregs in models of colitis and immune homeostasis (GITR, CD25, PD-1) (51).…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication from Ed Palmer’s group [67] demonstrated that expression levels of CD25, PD-1, and GITR reflect populations of Tregs with different degrees of self-reactivity: Triple hi Treg (high expression of all three mentioned markers) had increased CD5 and Nur77-GFP levels compared to Triple lo Tregs (low expression of these markers). Using B3K508 TCR transgenic T cells (that recognize peptides of different affinities), the Palmer group showed that ligands at the threshold of negative selection generate Triple lo cells, whereas very high-affinity peptides select Triple hi cells, suggesting that these two populations differ in their degree of affinity for self.…”
Section: Tonic Signaling and Peripheral T Cell Fitnessmentioning
confidence: 99%
“…These cells are maintained in vivo by self (and not foreign) antigens, as this population persists in antigen free mice , which lack infectious, microbial and dietary antigens. Functionally, self-reactive Tregs (Triple hi ) proliferated more in vivo and were more suppressive than Triple lo cells, whereas these lower affinity cells facilitated the conversion of conventional T cells into iTregs in a colitis model, although the mechnanism underlying this conversion has not yet been identified [67]. Collectively, these data suggest that the degree of self-reactivity in CD4 + conventional T cells, CD8 + T cells, and CD4 + regulatory T cells impacts their functional ability to respond to infection and control immune responses.…”
Section: Tonic Signaling and Peripheral T Cell Fitnessmentioning
confidence: 99%
“…Recent data demonstrated that the developing tTreg population is heterogeneous and contains at least two functionally diverse subpopulations. One of them (CD25 low GITR low PD-1 low tTreg) induced the emergence of pTreg that prevented intestinal inflammation [18] . It therefore appears that tTreg and pTreg have overlapping but nonredundant functions in vivo.…”
Section: Cns1mentioning
confidence: 99%